An analysis of river fragmentation by dams and river dewatering in Costa Rica. (22nd July 2020) - Farah‐Pérez, Aldo; Umaña‐Villalobos, Gerardo; Picado‐Barboza, Jorge; Anderson, Elizabeth P.
Abstract: Hydropower development is accelerating in the tropics, especially construction of small dams. Small dams are often classified as those lower than 15 m in height or with reservoir capacity less than 3 × 10 6 m 3 . Small dams frequently operate with water diversions from the main river channel, thereby affecting river connectivity through the creation of a dewatered reach. However, the extent and impact of dewatered reaches have been overlooked in most analyses of river fragmentation and dams to date. In Costa Rica, small dam development increased during the 1990s, ahead of current trends in other tropical regions. This study examined the effects of dams and their dewatered reaches on river connectivity at a national scale in Costa Rica. We adapted the Dendritic Connectivity Index and applied it to the four basins where over 80% of hydropower development has occurred. Our results showed that in two basins, the Sarapiqui and San Carlos, dewatered reaches contributed most to river fragmentation. In the Tarcoles and Reventazon basins, dams and dewatered reaches had similar effects on river fragmetnation. These different patterns can be explained by the spatial arrangement of dams in the individual river networks. We also found that dewatered reaches extended the elevation range of rivers affected by hydropower activity; this expansion was most significant in cases with interbasin water transfers. We discuss the implications of our findings on connectivity losses from dams for fishes whose range overlaps with hydropower activity. Our study may provide insights for other tropical countries with ongoing and future small dam development.